2022
DOI: 10.1039/d2cc04917a
|View full text |Cite
|
Sign up to set email alerts
|

Iron/photoredox dual catalysis for acyl nitrene-based C–O bond formation towards phthalides

Abstract: This paper describes an iron/photoredox dual-catalyzed acyl nitrene formation and the use of acyl nitrene in constructing various C-O bonds towards phthalides. The developed reaction starts from N-methoxyl-2-alkylbenzamides. Mechanism surveys...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
(15 reference statements)
2
9
0
Order By: Relevance
“…It has been established that the oxidation of N -acyloxyamide 1 under iron/photo dual catalysis enabled the formation of ferric acyl nitrene species A , 12 and our group recently showed intermediate A was an efficient partner in the nucleophilic substitution of 1,3-dicarbonyls, 12a b acyl nitrene/alkyne metalation, 12c and chloroamidation. 12d Besides, our previous work suggested that the nitrene species A 1 tended to undergo a dearomative ipso -cyclization.…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
“…It has been established that the oxidation of N -acyloxyamide 1 under iron/photo dual catalysis enabled the formation of ferric acyl nitrene species A , 12 and our group recently showed intermediate A was an efficient partner in the nucleophilic substitution of 1,3-dicarbonyls, 12a b acyl nitrene/alkyne metalation, 12c and chloroamidation. 12d Besides, our previous work suggested that the nitrene species A 1 tended to undergo a dearomative ipso -cyclization.…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
“…17 The intermolecular competition reaction between compound 1ab and its deuterated labeled analogue 1ab-d 2 was run in the same flask using our standard conditions. Following the procedure reported by Du Bois, a quantitative 13 C NMR experiment was conducted on the mixture of purified products. 3i Measurement of the ratio of 2a and 2a-d gave a KIE value of 0.86.…”
Section: Scheme 2 Scope and Limitations A Amentioning
confidence: 99%
“…(Scheme 1a). 13 We report herein our results for an original intramolecular iron-catalyzed C(sp 3 )-H lactonization reaction promoted by a 1,5-HAT process, without photoredox assistance. The reaction conditions developed are particularly sustainable: a catalytic amount of iron complex, the absence of external oxidants thanks to the use of hydroxylamines as nitrene source, and a reaction running in water in the presence of a hexafluoroisopropanol (HFIP) cosolvent restricted to 10%.…”
mentioning
confidence: 96%
“…Under similar iron/blue light conditions, Zhang et al disclosed an efficient procedure for the preparation of phthalides 126 from N -methoxyl-2-alkylbenzamides (Scheme 44c). 90 Mechanism investigations show that the reaction is initiated by the formation of iron nitrene species 125-A , followed by an iron nitrene-based hydrogen atom abstraction (HAA) and photoredox-neutral radical-polar crossover, and terminated by O -nucleophilic SN1 of 125-C to give the targeted phthalides. Although the role of light is still vague at the current stage, iron/photoredox dual catalysis deserves more attention because exogenous photosensitizers are unnecessary.…”
Section: Photo-induced Nitrene Transfermentioning
confidence: 99%